STUDENTS’ RELIGIOUS TOLERANCE: Comparing Muslim Students at Public Schools and Pesantren (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
Due to modernization and globalization, Indonesian Muslims today face complicated difficulties related to cultural diversity. The moderation allows Muslims to learn the religion from a variety of sources both inside and outside of school. Religious education is typically taught in public schools, boarding schools, and madrasas. This article aims to identify the religious tolerance among students at public schools and Pesantren. The study also examines the causes of the tolerable inequalities among students in three different school categories by putting the phenomenon in a social and policy context. The Data were collected by distributing survey to 926 students in 2021 in North Sulawesi. According to the findings, Muslim students in public schools and public madrasas are significantly more tolerant than those at Pesantren, and both groups of students are equally tolerant. Our understanding of how educational policies affect Muslim students’ religious tolerance outside of Java has been expanded by this surprising finding.